Answer:
y = (-2/5)x - 2
Step-by-step explanation:
One way to attack this problem is to interchange the coefficients of x and y and change the sign of one to +: 5x - 2y = -6 becomes 2x + 5y = c. Solving for the slope, m, we get 5y = -2x + c first, and then y = (-2/5)x + D.
Subbing 5 for x and -4 for y, we now have -4 = (-2/5)(5) + D.
Then -4 = -2 + D, so that D = -2.
The desired equation is thus y = (-2/5)x - 2.
Check: Does this pass through (5, -4)? Is -4 = (-2/5)(5) - 2 true? Yes.
Is the slope -2/5 the negative reciprocal of 5/2? Yes, it is.
Answer:
Step-by-step explanation:
The first differences of the sequence are ...
- 5-2 = 3
- 10-5 = 5
- 17-10 = 7
- 26-17 = 9
- 37-26 = 11
Second differences are ...
- 5 -3 = 2
- 7 -5 = 2
- 9 -7 = 2
- 11 -9 = 2
The second differences are constant, so the sequence can be described by a second-degree polynomial.
We can write and solve three equations for the coefficients of the polynomial. Let's define the polynomial for the sequence as ...
f(n) = an^2 + bn + c
Then the first three terms of the sequence are ...
- f(1) = 2 = a·1^2 + b·1 + c
- f(2) = 5 = a·2^2 +b·2 + c
- f(3) = 10 = a·3^2 +b·3 +c
Subtracting the first equation from the other two gives ...
3a +b = 3
8a +2b = 8
Subtracting the first of these from half the second gives ...
(4a +b) -(3a +b) = (4) -(3)
a = 1 . . . . . simplify
Substituting into the first of the 2-term equations, we get ...
3·1 +b = 3
b = 0
And substituting the values for a and b into the equation for f(1), we have ...
1·1 + 0 + c = 2
c = 1
So, the formula for the sequence is ...
f(n) = n^2 + 1
__
The 20th term is f(20):
f(20) = 20^2 +1 = 401
_____
<em>Comment on the solution</em>
It looks like this matches the solution of the "worked example" on your problem page.
M∠ABC=180°
7x+x-4 = 180
8x = 180+4
8x=184
x=184:8
x=23
∠DBС = x-4 = 23-4 = 19°
Answer: 19°.
Answer: -10
Step-by-step explanation:
Simplifying
-3(y + 5) = 15
Reorder the terms:
-3(5 + y) = 15
(5 * -3 + y * -3) = 15
(-15 + -3y) = 15
Solving
-15 + -3y = 15
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '15' to each side of the equation.
-15 + 15 + -3y = 15 + 15
Combine like terms: -15 + 15 = 0
0 + -3y = 15 + 15
-3y = 15 + 15
Combine like terms: 15 + 15 = 30
-3y = 30
Divide each side by '-3'.
y = -10
Simplifying
16 dollars each because you do 8x5 which equals 40 and do 168-40 which equals 128 / 8 equals 16